KEMAMPUAN BERPIDATO DENGAN METODE EKSTEMPORAN - Amy Sabila, author (JURNAL PESONA, 2015)
This research was aimed to describe speech ability through extemporan speech method as it is. This research used descriptive qualitative method. The data were collected through oral test and asking the students to do a speech which the title and the text of the speech has been prepared. The technique used in this research was stratified proporsional random sampling. The researcher used this technique because the population of the research was heterogeneous. The data collecting technique was supportive literature, observation, and interview. The result of the research shown speech ability through extemporan speech method as follows: 1) pronunciation aspect was very good; 2) intonation aspect was good; 3) vocabulary aspect was good; 4) students view aspect was not good; 5) expression aspect was good; 6) loudness aspect was average; 7) fluency aspect was very good; 8) comprehension aspect was not good. According to the result of the research, it can be concluded that speech ability through extemporan speech method was good because only a few errors found in each aspect.Keywords: Speech Ability, Extemporant Method